Efektivitas Program Syarhil Qur’an di LPTQ Provinsi Sumatera Utara Sebagai Media Dakwah dan Pemberdayaan Remaja - Nugraha, Babang Prima; Munandar, Munandar; Hasibuan, Riza Sakhbani; Simamora, Pimpinan Abaik; Azizah, Lisa Nur; Inggria, Annisa (CV. PUSDIKRA MITRA JAYA, 2025)
This study aims to analyze and measure the effectiveness of the syarhil Qur’an program at LPTQ North Sumatra as a medium of da’wah and its contribution to youth empowerment. The study focuses on the implementation of the syarhil Qur’an program conducted by LPTQ North Sumatra and the responses of experts and participants who have taken part in the syarhil Qur’an competition in the Musabaqah Tilawatil Qur’an (MTQ). This research applies a mixed-method approach, combining qualitative and quantitative research to produce comprehensive findings. Data collection techniques include structured interviews to obtain qualitative data related to program implementation and a questionnaire survey via Google Forms distributed to participants to gather quantitative data on the effectiveness of syarhil Qur’an as a medium of da’wah and youth empowerment. The study’s findings indicate that the implementation of the syarhil Qur’an program at LPTQ North Sumatra is based on two main aspects: planning and management, as well as coaching methods. In terms of planning and management, the program is considered effective due to the presence of a Training Center (TC) and a strong support system. However, the coaching method is still manual-based, making it less effective. Additionally, syarhil Qur’an as a medium of da’wah and youth empowerment is deemed effective in the learning aspect and has received positive public responses. Nevertheless, its impact on youth empowerment has not shown significant progress. Therefore, this study recommends developing more modern and systematic coaching methods to enhance program effectiveness.